Carbohydrate-dense snacks are a key feature of the nutrition transition among Ghanaian adults: findings from the RODAM study - Assmus, Frauke; Galbete, Cecilia; Knueppel, Sven; Schulze, Matthias B.; Beune, Erik; Meeks, Karlijn; Nicolaou, Mary; Amoah, Stephen; Agyemang, Charles; Klipstein-Grobusch, Kerstin; Bahendeka, Silver; Spranger, Joachim; et al. (Food & nutrition research, 2021)
Background: African populations in sub-Saharan Africa and African migrants in Europe are facing a rapid upsurge in obesity. This trend has been related to urbanization, migration and associated shifts in lifestyle, including dietary habits. Whether changes in eating patterns contribute to the rising burden of obesity among African populations is currently unknown. - Objective: Our aims in conducting this study were to characterize eating patterns among Ghanaian adults living in their country of origin and in Europe and to explore associations of meal patterns with body mass index (BMI). - Design: Within the cross-sectional RODAM (Research on Obesity and Diabetes among African Migrants) study, data of single 24-h dietary recalls from Ghanaian adults in rural Ghana (n = 20), urban Ghana (n = 42), and Europe (n = 172) were recorded. Eating frequencies, energy intake, and macronutrient composition of eating occasions (EOs, i.e. meals or snacks) were compared between study sites based on descriptive statistics and χ2-/Kruskal-Wallis tests. - Results: A rising gradient of EO frequencies from rural Ghana through urban Ghana to Europe was observed, mainly reflecting the differences in snacking frequencies (≥1 snack per day: 20 vs. 48 vs. 52%, P = 0.008). Meal frequencies were similar across study sites (≥3 meals per day: 30 vs. 33 vs. 38%, P = 0.80). Meals were rich in carbohydrates (median 54.5, interquartile range (IQR): 43.2-64.0 energy%) and total fats (median: 27.0, IQR: 19.9-34.4 energy %); their protein content was lowest in rural Ghana, followed by urban Ghana and Europe (P = 0.0005). Snacks mainly contained carbohydrates (median: 75.7, IQR: 61.0-89.2 energy%). In linear regression analyses, there was a non-significant trend for an inverse association between snacking frequencies and BMI. - Discussion and conclusions: The observed integration of carbohydrate-dense snacks into the diet supports the growing evidence for a nutrition transition among African populations undergoing socioeconomic development. This analysis constitutes a starting point to further investigate the nutritional implications of increased snacking frequencies on obesity and metabolic health in these African populations.